Controversies over the moral justification for patent protection in biotechnology - Adam Karbowski (Annales. Ethics in Economic Life, 2018)
This paper discusses the controversies over the moral justification for patent protection in biotechnology. Special emphasis has been put on the controversy over the moral justification for patent protection of stem cells. By referring to arguments for (1) human dignity and (2) patentability criteria, the moral justifiability of patent protection of stem cells is in serious doubt. A whole section of the paper is devoted to the moral issues linked to patent protection in biotechnology and their political and economic significance. An attempt is made to solve some of the discussed problems, i.e., the introduction of decision criteria based on the system of values shared by the members of a given society.
Keywords: K11; 330; Moral justification; Patents; Biotechnology